Pengaruh Kompetensi Sumber Daya Manusia, Penerapan Sistem Akuntansi Keuangan Desa, dan Pemanfaatan Teknologi Informasi Terhadap Kualitas Laporan Keuangan Desa (Studi Pada Perangkat Desa Se Kecamatan Banjaran Kabupaten Majalengka) - R. Neny Kusumadewi (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2020)
This study aims to see the effect of Human Resource Competence, Implementationof Financial Accounting Systems, Utilization of Information Technology on the Quality ofVillage Financial Reports in Banjaran District, Majalengka Regency. The research methodused a survey method with descriptive and verification approaches. The population in thisstudy was the village apparatus of the Banjaran District with a total sample of 65respondents. The data analysis used in this study is the classical assumption test, multiplelinear regression analysis, the coefficient of determination, and hypothesis testing, namelythe partial test (t test) and simultaneous test (F test). The results of the study partially showthat Human Resource Competence does not have a significant effect on Village FinancialStatements, while the Implementation of Village Financial Accounting Systems andUtilization of Information Technology partially have a significant effect on the Quality ofVillage Financial Reports. Simultaneous testing shows that Human Resource Competence,Implementation of Village Financial Accounting Systems and Utilization of InformationTechnology have a significant effect on the Quality of Village Financial Reports.